Who carries the Burden of Reproductive Health and AIDS Programs? - Evidence from OECD Donor Countries - Hendrik P. van Dalen (Tinbergen Institute, 2006)
This paper tries to establish who carries the burden in supporting reproductive health and AIDS programs worldwide. The 1994 International Conference of Population and Development (ICPD) in Cairo established goals for the expansion of assistance in matters of reproductive health and AIDS. This global effort has so far not sufficiently been supported by funds and this paper looks at what lies behind the level of funds and the sharing of financial burdens. Panel data on expenditures for population and AIDS activities funded by 21 donor countries for the years 1983-2002 are examined by means of dynamic panel data estimation. On an aggregated scale small donors 'exploit' the large donors: large donors give more resources than their 'fair share', i.e. their income weight in the group of donors. However, this picture is not true for the finance and support for multilateral organizations where every donor country pays its fair share. The exploitation hypothesis is true for the cases of bilateral aid and NGOs. The exploitation model gives however a partial view of what determines the sharing of burdens. To understand burden sharing across countries fully one needs to take account of the most dominant religions in a country, the pro-foreign aid stance of a government and the government size. Donor countries are not much affected in their funding behavior by the state of development of the least developed countries.
Keywords: D74; F35; D78; O19; 330; Foreign aid; donors; health; HIV/AIDS; global collective action; free rider